Progress in the Biomedical Application of Biopolymers: An Overview of the Status Quo and Outlook in Managing Intrauterine Adhesions - Philbert Nshimiyimana; Ian Major; Declan Mary Colbert; Ciara Buckley (Macromol)
Advancements in material science have made biopolymers a reliable solution in treating diseases for which there were no effective treatments. Intrauterine adhesions (IUAs) are the second leading cause of secondary infertility among women of reproductive age. Despite their negative impacts, the available data reveal that there is currently no effective treatment. This work serves to provide an overview of the progress in the biomedical application of biopolymers focusing on the clinical management of IUAs. Hysteroscopic adhesiolysis remains the standard treatment for IUAs, even though it is linked to recurrence and suboptimal reproductive outcomes. Efforts to improve IUAs treatment by combining hysteroscopy with adjuvants like physical barriers have not resulted in better outcomes. Biopolymers like hyaluronic acid (HA) represent a groundbreaking shift in regenerative medicine and have been used as anti-adhesives in the treatment of IUAs. This is attributed to their excellent biocompatibility, cell adhesiveness, biodegradability, low toxicity, and cell growth promotion ability. This study examines naturally occurring biopolymers, underscoring their biomedical applications, and limitations such as poor mechanical properties, rapid degradation, limited residence time, and bioavailability. Drawing from existing evidence and authors’ standpoints, innovative approaches harnessing the power of biopolymer engineering are suggested as future directions to overcome ongoing limitations.